Ecological Restoration in West China: Problems and Proposals - Wang, Xiuhong; Shen, Yuancun (Ambio, 2009)
Upper Paleozonic thick-bedded limestone strata are widely distributed and karst topography is well developed, which results in the region being prone to strong stony desertification. Because of unstable soil-forming conditions, other mountainous regions without limestone strata are also subject to serious water erosion, mud flow, and hill creep. According to statistical report, West China had a salinized cropland area of 20 754 kmsup 2, which occupied 6.5% of its total cropland area, and amounted to 27.2% of the nation's salinized cropland area (7).\n Thus, it is imperative to establish an integrated management system for ecological restoration entirely controlled by the central government.